The essence of authority and legal certainty of district courts in the execution of equitable consignment - Muhammad Alfi Sahrin Usup; Merry E. Kalalo; Wulanmas A. P. G. Frederik; Jemmy Sondakh (International Journal of Law, Environment, and Natural Resources, 2026)
The main issue that needs to be emphasized in the background of this study is the potential inconsistency between consignment as a mechanism for releasing debtors from their obligations and the disputable nature of such release prior to creditor acceptance or a court determination. This inconsistency has direct implications for the normative question of whether consignment, particularly at the execution stage by the District Court, fulfills the principles of legal certainty, justice, and balance. This issue logically leads to the focus of the research concerning the nature of the authority and legal certainty of the District Court in the execution of equitable consignment. The research problems addressed in this study are: (1) What is the nature of the authority and legal certainty of the District Court in the execution of equitable consignment?; (2) How does the urgency of the District Court’s authority affect legal certainty in the execution of consignment?; and (3) What is the ideal concept of authority and legal certainty of the District Court in the execution of equitable consignment? This study is a normative juridical legal research with a prescriptive approach. The discussion in this research explains that the nature of the authority and legal certainty of the District Court in the execution of equitable consignment demonstrates that executorial authority must be understood as a combination of normative validity and procedural legitimacy. Furthermore, the urgency of the District Court’s authority in influencing legal certainty in the execution of consignment lies in the fact that normative and institutional uncertainty at the execution stage directly transforms consignment from an instrument of certainty into a source of further uncertainty. Finally, the ideal concept of authority and legal certainty of the District Court in the execution of equitable consignment requires an executorial authority model that is independent, final and binding, effective yet proportional, and not deterministically dependent on external variables, while integrating law enforcement, legal protection, and social justice orientation.